FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA INTIAL PUBLIC OFFERING (IPO) DI BEI PERIODE TAHUN 2013-2017 - Suwandi Suwandi (Universitas Sang Bumi Ruwa Jurai, 2018)
The purpose of this study was to determine the effect of firm size, firm age, the percentage of shares offered, underwriter reputation, financial leverage, and ROE (Return On Equity) to the underpricing of stock in an Initial Public Offering (IPO). The data used are secondary data that did IPO companies listed on the Indonesian Stock Exchange (BEI) in 2013-2017. Analysis data technique used multiple linear regression. The results showed that the ROE (Return On Equity) has a significant effect on underpricing and variables of firm size, firm age, the percentage of shares offered, underwriter reputation, financial leverage insignificant effected on underpricing.The results of simultaneously F test showed that there was a significant difference between firm size, firm age, the percentage of shares offered, underwriter reputation, financial leverage, and ROE (Return On Equity) on underpricing of IPO shares.